Sosialisasi Penertiban Pedagang Kaki Lima (PKL) di Jalan Permindo dan Pemanfaatan Ruang Publik Berdasarkan Peraturan Daerah Kota Padang Tentang Ketertiban Umum - Fathirizqi, Ariq Naufal; Mardhatillah, Annisa; Putri, Febrina Amelda; Thahira, Putri Alya; Azura, Ayu; Nisa, Sarah Hilyatun; Niandra, Abief; Putra, Kiki Fadhila; ., Ikhsan; Anelda, Dafa; Husna, Zahwatul; Maharani, Putri; Dahayu, Helga Putri; Marwenny, Elwidarifa (GLOBAL SCIENTS PUBLISHER, 2026)
The presence of Street Vendors (PKL) on Permindo Street, Padang City, often creates a conflict between economic interest and the function of public space. Socialization indicates that many vendors still utilize sidewalks and roadsides in a way that obstructs pedestrian access and causes traffic congestion, violating the Regional Regulation (perda) of Padang City Number 11 of 2005 concerning Public Order. As a preventive and persuasive effort, a socialization activity was conducted for PKL in the Permindo area through direct dialogue and educational dissemination regarding the importance of public space functions. This activity aims to analyze the legal awareness of vendors and the effectiveness of socialization in realizing an orderly urban environment. The results show that while vendors understand the regulations, economic factors remain the primary challenge. Consistent socialization and the provision of relocation solutions are expected to be strategic steps in maintaining public order without neglecting the community’s economy.